Efficient Fractionation of Lignin- and Ash-Rich Agricultural Residues Following Treatment With a Low-Cost Protic Ionic Liquid - Chambon, Clementine L.; Chen, Meng; Fennell, Paul S.; Hallett, Jason P. (Frontiers in Chemistry, 2019)
Agricultural residues from rice, wheat and sugarcane production are annually available at the gigaton-scale worldwide, particularly in Asia. Due to their high sugar content and ash compositions, their conversion to bioethanol is an attractive alternative to their present disposal by open-field burning and landfilling. In this work, we demonstrate application of the low-cost protic ionic liquid triethylammonium hydrogen sulfate ([TEA][HSO4]) for pretreatment of rice straw, rice husk, wheat straw and sugarcane bagasse. The feedstocks had high ash (up to 13 wt%) and lignin content (up to 28 wt%). Pretreatment effectiveness was examined at 150 and 170°C and an optimal pretreatment time was identified and characterized by glucose release following enzymatic saccharification (i.e., hydrolysis), biomass delignification observed by compositional analysis, and lignin recovery. The isolated lignin fractions were analyzed by 2D HSQC NMR to obtain insights into the structural changes occurring following ionic liquid pretreatment. After treatment at 170°C for 30–45 min, enzymatic hydrolysis of three agroresidues gave near-quantitative glucose yields approaching 90% while rice husk gave 73% yield. Glucose release from the pulps was enhanced by saccharifying wet pulps without an air-drying step to reduce hornification. According to pulp compositional analysis, up to 82% of lignin was removed from biomass during pretreatment, producing highly digestible cellulose-rich pulps. HSQC NMR of the extracted lignins showed that delignification proceeded via extensive cleavage of β-O-4′ aryl ether linkages which was accompanied by condensation reactions in the isolated lignins. The high saccharification yields obtained indicate excellent potential for valorization of low-cost agroresidues in large volumes, which is promising for commercialization of biofuels production using the ionoSolv pretreatment technology.